2017
DOI: 10.1186/s12864-017-4350-x
|View full text |Cite
|
Sign up to set email alerts
|

Isogenic mice exhibit sexually-dimorphic DNA methylation patterns across multiple tissues

Abstract: BackgroundCytosine methylation is a stable epigenetic modification of DNA that plays an important role in both normal physiology and disease. Most diseases exhibit some degree of sexual dimorphism, but the extent to which epigenetic states are influenced by sex is understudied and poorly understood. To address this deficit we studied DNA methylation patterns across multiple reduced representation bisulphite sequencing datasets (from liver, heart, brain, muscle and spleen) derived from isogenic male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…However, we have seen that no differentially methylated autosomal CpG sites between sexes, except one, contained androgen response elements, indicating that DNA methylation due to sex in the liver might be independent of testosterone. Moreover, sex hormones have been shown not to influence DNA methylation in human leukocytes or in mice liver ( 49 , 56 ). Notably, Mayne et al ( 45 ) reported that two-thirds of autosomal genes that were sex biased in the human liver were not under direct influence of sex hormones, which suggests there are other mechanisms driving hepatic sex differences, such as epigenetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have seen that no differentially methylated autosomal CpG sites between sexes, except one, contained androgen response elements, indicating that DNA methylation due to sex in the liver might be independent of testosterone. Moreover, sex hormones have been shown not to influence DNA methylation in human leukocytes or in mice liver ( 49 , 56 ). Notably, Mayne et al ( 45 ) reported that two-thirds of autosomal genes that were sex biased in the human liver were not under direct influence of sex hormones, which suggests there are other mechanisms driving hepatic sex differences, such as epigenetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The most extensively profiled sexually dimorphic epigenetic mark is DNA methylation. Sex-specific methylation patterns have been observed in blood [74][75][76][77], placenta [78], liver [79][80][81][82], pancreas [83], muscle [84], heart [81], and brain [81,[85][86][87][88][89]. Sex differences in histone modifications have also been described, although thus far only in mouse brain [90,91].…”
Section: Sex Differences In Epigeneticsmentioning
confidence: 99%
“…The threshold of methylation differences is another parameter that can be tweaked in detecting sDMR. Therefore, we used a 20% threshold for methylation differences, which has been used by other groups in their studies of sex-biased methylation in mice [18,71].…”
Section: Methodology For Identifying Sdmc and Sdmr And Its Impact On mentioning
confidence: 99%